PHYTOCHEMICAL SCREENING OF AGLAIA ELAEAGNOIDEA AND THEIR EFFICACY ON ANTIOXIDANT AND ANTIMICROBIAL GROWTH - Manjari, *G.; Saran, S.; Baskara Rao, A. Vijaya; Devipriya, Suja. P (International Journal of Ayurveda and Pharma Research, 2017)
Phytochemicals are extensively found at different levels in many plants and serves as basic raw material in the manufacturing of medicine, nutrition, cosmetics, dyeing and other industries. The present study aimed to lighten the medicinal uses of the leaves and stem bark of Aglaia elaeagnoide plant in the treatment of different ailments such as astringent, antidiarrhoeal, antidysenteric, skin diseases, tumours in Indian medicine of Ayurveda. In the present work we investigated the phytochemical screening to find out new sources of natural antioxidant and antimicrobial activity source from the leaf and stem bark of Aglaia elaeagnoidea with different solvents such as chloroform, ethanol, methanol, petroleum ether and water. Phytochemical screening of all crude extracts of leaf and bark reveals the presence of alkaloids, steroids, phenols, flavonoids, tannins, coumarins, quinones, xanthoproteins, terpinoids, carbohydrates, fatty acids, leucoanthocyanins, saponins and emodins. In vitro antioxidant activity of ethanolic extracts of leaf and bark exhibited maximum phenolic compounds and scavenging activity. Phenolic compounds of leaf and bark exhibit positive correlation to antioxidant activity. All the crude extracts of leaf and bark showed low to moderate inhibition zone against Staphylo coccus aureus, Bacillus subtilis, Escherichia coli, Vibrio vulnificus and Candida albicans. The antioxidant and antimicrobial activity of different crude extracts of bark exhibited more efficacy compared to the leaf extracts. Thus, further development of new phytochemicals for the treatment of different disorders by using sustainable approach opens up possibilities in the usage of these as antioxidant and antimicrobial in various medicinal composition.